2010
DOI: 10.1002/app.31515
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel aromatic polyamides with xanthene cardo groups

Abstract: Two novel monomers, 9,9-bis[4-(4-carboxyphenoxy)phenyl]xanthene (BCAPX) and 9,9-bis[4-(4-aminophenoxy)phenyl]xanthene (BAPX) were prepared in two main steps starting from nucleophilic substitution of 9,9-bis(4-hydroxyphenyl)xanthene (BHPX) with p-fluorobenzonitrile and p-chloronitrobenzene, respectively. Using triphenyl phosphite and pyridine as condensing agents, two series of polyamides containing xanthene cardo groups with the inherent viscosities (0.82-1.32 dL/g) were prepared by polycondensation from BCAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…First of all, 10,10-bis(4-hydroxy-3-methylphenyl)-9(10 H )-anthrone ( 1 ) was prepared in good yield via one-pot, two-step synthetic procedure by reaction of 9(10 H )-anthrone with thionyl chloride, affording 10,10-dichloro-9(10 H )-anthrone, followed by treatment with o -cresol in the refluxing xylene using a similar method. 16 But it should be noted that the expected product, 9,9-bis(4-hydroxy-3-methylphenyl)-9,10-dihydroanthracene ( 1′ ), was not obtained under the same conditions. Secondly, reaction of bisphenol intermediate ( 1 ) with 4-chloronitrobenzene in the presence of potassium carbonate afforded the dinitro compound, 10,10-bis[4-(4-nitrophenoxy)-3-methylphenyl]-9(10 H )-anthrone ( 2 ).…”
Section: Monomer Synthesismentioning
confidence: 97%
See 1 more Smart Citation
“…First of all, 10,10-bis(4-hydroxy-3-methylphenyl)-9(10 H )-anthrone ( 1 ) was prepared in good yield via one-pot, two-step synthetic procedure by reaction of 9(10 H )-anthrone with thionyl chloride, affording 10,10-dichloro-9(10 H )-anthrone, followed by treatment with o -cresol in the refluxing xylene using a similar method. 16 But it should be noted that the expected product, 9,9-bis(4-hydroxy-3-methylphenyl)-9,10-dihydroanthracene ( 1′ ), was not obtained under the same conditions. Secondly, reaction of bisphenol intermediate ( 1 ) with 4-chloronitrobenzene in the presence of potassium carbonate afforded the dinitro compound, 10,10-bis[4-(4-nitrophenoxy)-3-methylphenyl]-9(10 H )-anthrone ( 2 ).…”
Section: Monomer Synthesismentioning
confidence: 97%
“…There is no doubt that ideal structure modification of polymer is expected to provide balanced properties of high thermal stability and good processability. It has been demonstrated that PAs bearing bulky cyclic side groups (usually named as cardo groups) such as fluorene, 11 –13 phthalide, 14 tert -butylcyclohexylidene, 15 xanthene, 16,17 or cyclopentylidene 18 can exhibit a significant increase in both glass transition temperature ( T g ) and thermooxidative stability while providing good solubility. The 9(10 H )-anthrone structure as a bulky pendent group was previously incorporated into the polymer backbones of the PAs and polyimides to improve their processability based on 10,10-bis(4-aminophenyl)-9(10 H )-anthrone monomer.…”
Section: Introductionmentioning
confidence: 99%
“…Jian et al [48] and Sheng et al [59] described the synthesis of aromatic polyamides containing ether and bulky xanthene groups from a diacyl chloride monomer, 9,9-bis[4-(chloroformylphenoxy)phenyl]xanthene, or a diamine monomer, 9,9-bis[4-(4-aminophenoxy) phenyl]xanthene (Scheme 29, P52-P53). The polyamides were amorphous and soluble in polar Palí et al [139] reported on the study of the influence of controlled structural modifications on physical and conformational properties of isomeric aromatic polyamides with different bulky pendant lateral groups (Scheme 28, P51).…”
Section: Scheme 25 Aramids With Enhance Solubility Containing Bulky mentioning
confidence: 99%
“…The polymers, with ether and bulky xanthenes groups (η inh from 0.72 to 0.98 dL/g), showed good mechanical properties (tensile strengths ranging from 82 to 106 MPa, elongations at break from 10 to 25%, and initial moduli from 2.0 to 2.8 GPa). Sheng et al [ 59 ] also described the preparation of aramids with xanthene moietis, starting from 9,9-bis[4-(4-carboxyphenoxy) phenyl]xanthene and 9,9-bis[4-(4-aminophenoxy) phenyl]xanthene. The polymers had η inh from 0.82 to 1.32 dL/g and gave flexible and transparent films by casting (moduli from 2.15 to 2.63 GPa, tensile strengths ranging from 86 to 109 MPa and elongations at break from 13 to 22%).…”
Section: Aromatic Polyamides With Selected Properties and Applicatmentioning
confidence: 99%
See 1 more Smart Citation